OPTIMIZED ENERGY EFFICIENT SOLUTION WITH STAND ALONE PV SYSTEM - Charan, Chandragiri Radha; Laxmi, A Jaya; Sangeetha, P (MATTER: International Journal of Science and Technology, 2017)
Photovoltaic systems are presenting an alternative source for production of electricity in a sustainable way. PV systems are a form of renewable energy systems that are progressively being used for efficient production of electricity. PV systems in the form of Stand Alone systems offer a potential solution to generate clean electricity with minimization of all form of losses. This system consists of PV array, battery, inverter and load. Its performance depends on orientation of PV array, horizon, irradiance, shading, the local climate, wind speed and direction and inverter performance. The I-V characteristics of the system are affected by shading of module and varying irradiance levels. The simulation model of Stand Alone PV System design using PVsyst software to perform the full analysis of PV systems is presented in this paper. The energy output throughout the year was simulated. The system loss diagram represents the efficiency of conversion and total energy output.